Intestinal ischaemia associated with carcinoid tumor: a case report with review of the pathogenesis - Yener, O (Prague Medical Report, 2013)
Carcinoid tumors are rare, slow-growing neuroendocrine neoplasms that are often indolent and may not become clinically apparent until there is a metastatic spread or evidence of carcinoid syndrome. A 44-year-old man presented to our clinic department with a history of previous left colon cancer operation, chronic crampy left lower quadrant pain, mass and severe anemia. A MR scan was obtained which demonstrated a calcified mesenteric mass 12×8×10 cm diameter with surrounding left colon mesenteric infiltration. The liver was normal. A case of ischaemic ileal necrosis is reported. It was associated with elastic vascular sclerosis produced by mesenteric metastases of an ileal carcinoid tumor. It is postulated that intestinal ischaemia may be of more importance in the production of abdominal pain by carcinoid tumors than has been generally accepted, and that it is the result of functional and structural changes in and around the mesenteric blood vessels, caused by substances secreted by the carcinoid tumor.
Keywords: nádory ilea; střeva; lidé; Carcinoid Tumor; Ischemia; Adult; Intestines; Male; ischemie; dospělí; Ileal Neoplasms; karcinoid; Humans; mužské pohlaví